The main types of information units conveyed by the present perfect, past indefinite and past perfect and how to teach them - Kuzmickaitė , E. (Psichologija, 1971)
The tense systems of the English and Lithuanian languages differ in the degree of precision with which the same events are characterized. Owing to a more differentiated system of tense forms in the English language, one can convey such information about actions which is not grammatically expressed in the mother tongue. The main types of information units conveyed by the Present Perfect are described in the article. They are compared to those in Lithuanian. Such contrasting analysis exposes the difference between the two languages and shows the difficulties experienced by Lithuanian students in mastering the Present Perfect. In teaching the tense forms the teacher acquaints the students with the types of information the studied tense form can convey. The contrasting analysis with Lithuanian exposes the factors conditioning the choice of a tense form in the two languages. The exercises aimed at developing the students’ skill of using tense forms in speech are built in such a way that the specific difficulties induced by the mother tongue are taken into account.